2020
DOI: 10.1016/j.cdtm.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Screening of long non‐coding RNAs markers in plasma of children with chronic gastritis

Abstract: ObjectiveThe study aimed to detect and analyze long non‐coding RNAs (lncRNAs) in plasma of children diagnosed with chronic gastritis, and to explore its biological functions and involved signaling pathways.MethodsThe plasma samples were collected from six children that were diagnosed with chronic gastritis by physical examination, gastroscopy, and pathological examination and six healthy children. The plasma samples were assayed for determining the expression profiles of lncRNA based upon the gen chip detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Besides various electronic and information technologies, the biological molecule is becoming an integral part of research on many other GI diseases. [ 57 , 58 , 59 ] Accordingly, we believe that it will also optimize the diagnosis of SNADETs. With the rapid advances in both “hardware” and “software,” the technological revolution will contribute to the increasing awareness and recognition of SNADETs.…”
Section: Endoscopic Diagnosis For Snadetsmentioning
confidence: 99%
“…Besides various electronic and information technologies, the biological molecule is becoming an integral part of research on many other GI diseases. [ 57 , 58 , 59 ] Accordingly, we believe that it will also optimize the diagnosis of SNADETs. With the rapid advances in both “hardware” and “software,” the technological revolution will contribute to the increasing awareness and recognition of SNADETs.…”
Section: Endoscopic Diagnosis For Snadetsmentioning
confidence: 99%
“…Gastritis adalah peradangan selaput lambung yang disebabkan oleh kombinasi dari berbagai macam faktor, termasuk infeksi Helicobacter pylori (H. pylori) [1]. Kondisi tersebut dapat menjadi masalah akut atau kronis yang meningkatkan risiko pada kondisi lain, seperti radang lambung, perdarahan, atau kanker [2].…”
Section: Pendahuluanunclassified
“…Given the high blood stability and detection sensitivity of lncRNAs in plasma compared with several traditional protein biomarkers, 29 circulating lncRNAs show promising roles as adjunct diagnostic/prognostic epigenetic biomarkers in several disorders, including inflammatory conditions. [30][31][32] In the last years, the circulatory MALAT1 expression profile was screened mainly in adults with sepsis. Pellegrina et al identified that deregulated MALAT1 expression might "contribute to gene expression changes associated with the poorer outcome of elderly patients with sepsis".…”
mentioning
confidence: 99%